Dealing with un(expected) ethical dilemma: experience from the field - Othman, Zaleha; Abdul Hamid, Fathilatul Zakimi (The Qualitative Report, 2018)
Despite the growing interest in qualitative research and discussion of ethics, there has been little focus in the literature on the specific ethical dilemmas faced by researchers. In this paper, we share our fieldwork experiences regarding the ethical dilemmas that we encountered while doing research on a sensitive topic. Specifically, we share some of the ethical dilemmas, that is, concerning confidentiality, anonymity, legitimacy, controversial data, interpretation and off-the-record data, which emerged from the research. Most importantly, this paper shares ideas concerning how researchers might deal with ethical issues while preserving their integrity in the research process. Overall, this paper suggests approaches that qualitative researchers can adopt when doing research on sensitive topics. The paper contributes towards closing an existing gap in the literature, making visible the challenges frequently faced by qualitative researchers, that is, the vulnerability of researchers while preserving research integrity. Finally, this paper concludes with the suggestion that ethical dilemmas are part of the research process in doing qualitative research. However, it is suggested that future research should focus on ethical issues from the perspective of the researchers as well as the respondents.